Liminal: A Collection of Short Stories and Analysis - Shaw, Thomas Byam (Curtin University, 2024)
LIMINAL is a collection of short stories that attempts to combine the themes of ecology or ‘the Anthropocene’ and travel narratives through the aesthetic mode of the Weird. The collection opens with a series of short work before transitioning into a long-form interactive narrative: ‘Under, Under the Earth’. Following this is an exegesis explaining the theoretical synchronicities between its elements as well as to connect these elements to relevant bodies of theoretical and fictional work.